Az olasz nyelvi írásbeli szövegértés és szövegalkotás fejlettségének és néhány háttértényező hatásának vizsgálata gimnazisták körében - Majernik, Erzsébet (Magyar Pedagógia, 2012)
The paper analyses proficiency in Italian as a Foreign Language among Hungarian pupils in secondary (grammar) school Years 10 and 11. In a study conducted in May 2011, we investigated the learners’ reading comprehension and composition skills in that language. Following a discussion of factors that influence language proficiency and a survey of findings to date, we examine the development of the skills mentioned above for Italian. We then provide the personal, cognitive, affective, and within-school factors that affected the learners’ performance. Gender also had a significant effect on the findings in this study, as girls performed better than boys in every respect. Among within-school factors, marks in Italian and Hungarian Grammar classes provided significant explanatory power. Pupils who had already earned a certificate of language proficiency or knew more than one foreign language performed significantly better than their classmates. The correlation between performance on reading comprehension and composition tests and attitude toward the activity was very small. The usefulness of Italian was evaluatedas positive among the learners. Those who planned to sit for a proficiency exam in the language achieved significantly better results. We found a strong correlation between number of weekly class-hours and performance, particularly in composition. Learners who attended three classes a week of Italian performed significantly worse than their classmates who attended more. Among the classroom activities, test results were influenced by practice with composition tasks, vocabulary, and grammar. Among external factors, parents’ educational level had no effect on pupils’ language proficiency.